2017
DOI: 10.1186/s12885-017-3648-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ki67 and uPA/PAI-1 expression in intermediate-risk early stage breast cancers

Abstract: BackgroundThe objective of this study was to compare the efficacy of biomarkers in assessing the risk of breast cancer recurrence in patients with node-negative or micrometastatic grade II breast cancer. Specifically, we compared risk assessments based on the St. Gallen clinicopathological criteria, Ki67 expression and urokinase plasminogen activator (uPA)/plasminogen activator inhibitor-1 (PAI-1) expression.MethodsThis retrospective study included 347 patients with breast cancer followed at Limoges University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Individual Ki67 values were therefore not available for uni- and multivariate analysis. This is important in the light of two recent publications which demonstrated that Ki67 expression was lower in uPA/PAI-1-negative than in uPA/PAI-1-positive tumors [ 26 , 27 ]. Furthermore, the subset of patients with available and thus analyzable tumor tissue was only a relatively small fraction of the overall trial population of 3714 women who had been randomized into the trial, thus potentially obscuring a potential prognostic effect of the uPA/PAI1 ratio, simply because not enough DDFS events had occurred.…”
Section: Discussionmentioning
confidence: 97%
“…Individual Ki67 values were therefore not available for uni- and multivariate analysis. This is important in the light of two recent publications which demonstrated that Ki67 expression was lower in uPA/PAI-1-negative than in uPA/PAI-1-positive tumors [ 26 , 27 ]. Furthermore, the subset of patients with available and thus analyzable tumor tissue was only a relatively small fraction of the overall trial population of 3714 women who had been randomized into the trial, thus potentially obscuring a potential prognostic effect of the uPA/PAI1 ratio, simply because not enough DDFS events had occurred.…”
Section: Discussionmentioning
confidence: 97%
“…Links are known to exist between the Ki67 index and the values for uPA/PAI-1. Deluche et al found lower Ki67 indices with negative uPA/PAI-1 than with increased values, with the threshold between low and high Ki67 being set at 20% [ 22 ]. They observed that when both parameters were taken into account in therapy planning, 9% fewer patients were received a recommendation for adjuvant chemotherapy than in cases where only the St. Gallen criteria were used.…”
Section: Discussionmentioning
confidence: 99%
“…Spearman rank correlation was used to estimate the strength of association between tracer uptake and Ki-67. The threshold for high versus low Ki-67 was defined as 20%, based on a 2017 study of earlystage breast cancers (29) and the 2015 St. Gallen meeting consensus (30). In addition, a 14% Ki-67 threshold was also examined based on the earlier 2011 St. Gallen meeting consensus (31).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Representative images from tumors with a low and high Ki-67 proliferative status (Ki-67 , or $ 20%) (29,30) are shown in Figures 1 and 2, respectively. Plots of tumor SUV max grouped by high and low Ki-67 (n 5 29) are depicted in Figure 3A.…”
Section: Measurements Of 18 F-iso-1 Uptake and Association With Ki-67mentioning
confidence: 99%